Enhancing Teachers' Teaching Performance Through Social and Personality Competencies - Sabilah, Fardini; Andini, Thathit Manon (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study aims to examine the standards for social and personality competencies, identify the most critical personality variables, determine the indicators of these variables influencing teacher performance, and explore teachers' perspectives on these issues. A cross-sectional survey involving 165 middle school teachers from various regions in Indonesia was conducted. The survey data were triangulated through interviews and focus group discussions (FGDs) for deeper insights. Data analysis was performed using Smart-PLS 3, with findings visualized through regression and composite models. The findings highlight key competency standards, including effective, empathetic, and polite communication with educators (impact value: 0.180) and a wise personality (impact value: 0.128). The most significant personality variable identified was a teacher's sense of true life calling, showing a negative relationship with teaching performance (-0.290). Indicators of personality variables that significantly influenced teaching performance included appropriate dress compatibility (impact value: 0.102), respected behavior (impact value: 0.122), decisive speech (impact value: 0.194), swift attire presentation (impact value: 0.251), and a fit appearance (impact value: 0.098). From the teachers' perspectives, critical aspects of social and personality competencies that enhance teaching performance were effective communication with students and parents, a wise personality, and a strong sense of true life calling. These traits enable teachers to navigate challenges and adversities effectively.